Exploring the impact of environmental, social, and governance on clean development mechanism implementation through an institutional approach - Lee, Sue Kyoung; Choi, Gayoung; Roh, Taewoo; Lee, So Young; Um, Dan-Bi (Frontiers in Psychology, 2022)
The study hypothesizes that the environmental, social, and governance (ESG) of the host country have a significant effect on Clean Development Mechanism (CDM) implementation. As CDM incorporates sustainable development as one of the objectives for the green transition, many countries endeavor to adopt and implement CDM as their cleaner production method. Based on the institutional theory, the study aims to investigate the mechanism by which the institutional process of each ESG pillar makes an opportunity for a host country and to see how such country-specific factors influence the implementation of CDM projects. A county-year unbalanced sample drawn from World Bank and multinational CDM project data was analyzed using panel logistic and Poisson regression. Panel regression results show that high energy intensity and low renewable electricity output as an environmental pillar positively affect CDM implementation. Unemployment and undernourishment as a social pillar positively affect CDM while low government effectiveness and the high rule of law positively affect CDM. In the results of zero-inflated Poisson regression, the direction of government effectiveness was upturned. Findings have broadened and deepened the ESG pillar based on institutional theory and emphasized sustainable development rather than economic outputs.